Multi-temporal analysis of the Peru-Colombia fluvial border by satellite images analysis based on geographical objects during the period 1989-2015 (2020)
This paper proposes a semi-automated method to study the fluvial dynamics of large rivers using multi-temporal geographic object-based image analysis (GEOBIA), which provides direct interoperability with geographic information systems, allows quantifying the variation of existing landforms, and is efficient in terms of computing time. The method is applied to the dynamics of the Amazon River, which has provoked a conflict between Peru and Colombia for being the borderline that separates both countries. The results obtained show the repercussions on its surface such as changes in sand islands and erosion, as well as the dynamics at the channel bottom during the 1989–2015 period caused by the sediment load and thalweg movement. These results are verified against data collected on field, finding 99.2 % accuracy between estimates and actual figures.